SERVICII INOVATOARE ÎN BIBLIOTECI - PETRESCU, Lola Maria; TOPAN, Biblioteca Judeţeană „Octavian Goga” Cluj, Georgeta (BIBLIOPOLIS, 2020)
The works studied and used during the elaboration of the article show that libraries around the world are in constant motion, renewal, modernization – processes due to many challenges coming from outside of the institutions. The issues arising interest to library specialists are the same: the expansion and diversification of innovative and qualitative, user-driven services, but the opinions are divided in applying their trade loyalty strategies. The co-participation of users in offering service and promoting news, the library „3rd place”, the hybrid library that offers traditional services and Web 1.0 services, Web 2.0 and, in the future, maybe Web 3.0 and Web 4.0, determine the adoption of the model of participatory library and other new models for libraries of the future.